Pelatihan Koding dan Kecerdasan Buatan Melalui Python serta Generative AI di SMA PBB Arjasari Bandung - Eko Darwiyanto; Yudi Priyadi; Rio Nurtantyana (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
SMA PBB Arjasari, a private school in Arjasari District, Bandung Regency, employs 45 teachers and staff with varied educational backgrounds. Currently, Coding and Artificial Intelligence (AI) electives for grades X–XII are taught by a single teacher, which poses challenges in meeting the Ministry of Education and Culture curriculum outcomes. Interviews and needs analysis identified three key issues: limited structured resources, basic programming proficiency, and the use of Generative AI in learning. This community service activity aims to boost teacher competency through structured, hands-on training. Coding materials are sourced from open resources (e.g., w3schools); AI materials cover Generative AI concepts (ChatGPT, Gemini, Deepseek) and case studies from AI lectures. The program features three sessions: Generative AI for learning, basic Python programming, and solving AI case studies, each with coding practice. Methods include presentations, demonstrations, independent practice, and interactive quizzes. Impacts include 95% participant satisfaction, better AI understanding, improved basic programming skills, and greater readiness to achieve curriculum goals, according to post-activity surveys. Based on these results, the program can be replicated and expanded through further training.